2015
DOI: 10.1016/j.mineng.2015.05.010
|View full text |Cite
|
Sign up to set email alerts
|

Discrete element simulation of mill charge in 3D using the BLAZE-DEM GPU framework

Abstract: The Discrete Element Method (DEM) simulation of charge motion in ball, semi autogenous (SAG) and autogenous mills has advanced to a stage where the effects of lifter design, power draft and product size can be evaluated with sufficient accuracy using either two-dimensional (2D) or three-dimensional (3D) codes. While 2D codes may provide a reasonable profile of charge distribution in the mill there is a difference in power estimations as the anisotropic nature within the mill cannot be neglected. Thus 3D codes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
27
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 71 publications
(28 citation statements)
references
References 20 publications
1
27
0
Order By: Relevance
“…2(a) shows the benefits of Blaze-DEM in terms of increasing the number of particles in a simulation. We see that current DEM simulations did not correctly capture the behavior of what was being simulated, while Blaze-DEM gives a very good match to what is seen in reality [12,14]. Fig.…”
Section: Simulation Capabilitiesmentioning
confidence: 80%
See 3 more Smart Citations
“…2(a) shows the benefits of Blaze-DEM in terms of increasing the number of particles in a simulation. We see that current DEM simulations did not correctly capture the behavior of what was being simulated, while Blaze-DEM gives a very good match to what is seen in reality [12,14]. Fig.…”
Section: Simulation Capabilitiesmentioning
confidence: 80%
“…In [12,14] we applied the code to industrial ball mill and silo simulations respectively. The results obtained were in good agreement to experiment.…”
Section: Impactmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, because of the relative tangential velocity between the mill and the steel balls, the total collision energy calculated using the classic theory should consider the relative tangential velocity. 11,12 Currently, the kinematic characteristics of steel ball have been numerically simulated using discrete element methods [13][14][15][16][17][18][19] and experimentally investigated through sensor technology. [20][21][22][23][24][25][26][27] It was found that the operating parameters had a profound effect on the charge characteristics, 28 and the effect of operating variables on the optimum performance of the mill still needed to be addressed to enhance energy utilization.…”
Section: Introductionmentioning
confidence: 99%